A defined method for differentiating human iPSCs into midbrain dopaminergic progenitors that safely restore motor deficits in Parkinson’s disease - Nakamura, Ryota; Nonaka, Risa; Oyama, Genko; Jo, Takayuki; Kamo, Hikaru; Nuermaimaiti, Maierdanjiang; Akamatsu, Wado; Ishikawa, Kei-ichi; Hattori, Nobutaka (Frontiers in Neuroscience, 2023)
Parkinson's disease (PD) is a progressive neurodegenerative condition, primarily affecting motor functions; it is caused by the loss of midbrain dopaminergic (mDA) neurons. The therapeutic effects of transplanting human induced pluripotent stem cell (iPSC)-derived mDA neural progenitor cells in animal PD models are known and are being evaluated in an ongoing clinical trial. However, sorting mDA progenitors by cell surface antigens for purification is a rate-limiting step in the large-scale preparation of therapeutic products. This study aimed to investigate the usefulness of dopaminergic progenitor cells derived from human iPSCs by our reported method, which promotes differentiation and neuronal maturation by treating iPSCs with three inhibitors at the start of induction. Approximately ≥80 % of cells induced by this method without sorting expressed mDA progenitor markers and differentiated primarily into A9 dopaminergic neurons in vitro. After transplantation in 6-hydroxydopamine-lesioned PD model mice, >90 % of the engrafted cells differentiated into the lineage of mDA neurons, and approximately 15 % developed into mature mDA neurons without tumour formation. The grafted PD model mice also demonstrated significantly improved motor functions. Thus, the differentiation protocol for the preparation of mDA progenitors is a promising option for cell therapy in patients with PD.